An expert system based on wavelet decomposition and neural network for modeling Chua's circuit - Hanbay, Davut; Turkoglu, Ibrahim; Demir, Yakup (Pergamon-Elsevier Science Ltd, 2008)
This paper presents an expert system based on wavelet decomposition and neural network for modeling and simulation of Chua's circuit which is used for chaos studies. The problems which arise in modeling Chua's circuit by neural networks are high structural complexity and slow and difficult training. With this proposed method a new solutions is produced to solve these problems. Wavelet decomposition is used for new useful feature extracting from input signal and neural network is used for modeling. Test results of proposed wavelet decomposition and neural network model are compared with test results of neural network model. Desired performance is provided by this new model. Test results showed that the suggested method can be used efficiently for modeling nonlinear dynamical systems. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: expert systems; wavelet decomposition; neural networks; Chua circuits